Red Mud from Brazil: Thermal Behavior and Physical Properties - Pereira Antunes, Maria Lucia [UNESP]; Couperthwaite, Sara Jane; Conceicao, Fabiano Tomazini da [UNESP]; Costa de Jesus, Carolina Petrisin [UNESP]; Kiyohara, Pedro Kunihiko; Vieira Coelho, Antonio Carlos; Frost, Ray Leslie (Amer Chemical Soc, 2012)
The main constituents of red mud produced in Aluminio city (S.P., Brazil) are iron, aluminum, and silicon oxides. It has been determined that the average particle diameter for this red mud is between 0.05 and 0.002 mm. It is observed that a decrease in the percentage of smaller particles occurs at temperatures greater than 400 degrees C. This observation corresponds with the thermal analysis and X-ray diffraction (XRD) data, which illustrate the phase transition of goethite to hematite. A 10% mass loss is observed in the thermal analysis patterns due to the hydroxide-oxide phase transitions of iron (primary phase transition) and aluminum (to a lesser extent). The disappearance and appearance of the different phases of iron and aluminum confirms the decomposition reactions proposed by the thermal analysis data. This Brazilian red mud has been classified as mesoporous at all temperatures except between 400 and 500 degrees C where the classification changes to micro/mesoporous.